Formation of Teacher Expectations: Previous Student Performance and Teacher Characteristics as Explanatory Factors; [Formación de Expectativas Docentes: Rendimiento Previo del Estudiante y Características del Profesor Como Factores Explicativos] - Cardenas-Mancilla, M (Universidad Internacional de la Rioja, 2024)
Although the effect of teacher expectations on students’ academic performance has been verified, few studies have focused on establishing which factors affect the formation of these expectations, especially ones that consider previous student performance and the professional experience of the teacher as explanatory factors. The aim of this study was to examine the effect of these factors on the formation of teacher expectations. The sample comprised 21 teachers from 11 schools, with low, medium, and high experience levels, as well as 363 firstyear primary-school students from Chile (ages 6-7), whose academic performance was measured at the start of the school year. Teacher expectations were measured part-way through the school year. A mixed ANOVA analysis made it possible to assess whether teacher expectation varies depending on previous performance and teacher experience. The results indicated that previous performance and teacher experience both have a significant effect on how expectations form. However, the effect of experience varies depending on the different dimensions of the expectations. © 2024, Universidad Internacional de la Rioja. All rights reserved.